Influence of the properties of layer-by-layer active layers on forward osmosis performance - Qi, Saren (2013)
The advancement of forward osmosis (FO) technology requires separation membranes with appropriate transport characteristics. The layer-by-layer (LbL) method exhibits great flexibility for fabricating the active layer of FO membrane with controllable separation properties. The current work focused on investigating the effect of LbL active layer properties on the FO performance. A series of FO membranes were prepared with varied number of polyelectrolyte bilayers which were composed of positively charged poly(allylamine hydrochloride) (PAH) and negatively charged poly(sodium 4-styrene-sulfonate) (PSS), with either PAH or PSS as the terminating layer. The active layers were characterized in terms of contact angle, surface roughness, and zeta potential, which were exploited to explain the variations of the intrinsic transport properties (the hydraulic permeability and the solute permeability) of the polyelectrolyte multilayer films. FO filtration experiments were carried out to assess the performance of the same series of FO membranes. Both the filtration flux and the FO efficiency were demonstrated as a strong function of the LbL active layers. This dependency was rationalized by analyzing the relative importance of the different transport mechanisms during the FO processes, which were inherently correlated to the intrinsic transport properties of the multilayer films. The current investigation not only justifies the feasibility of improving the FO performance by properly controlling the number of the polyelectrolyte bilayers and the surface charge, but also makes the underlying mechanisms comprehensible.